The Patagonian Sublime : The Green Economy and Post-Neoliberal Politics - Mendoza, Marcos (Book collections on Project MUSE., 2018)
"The Patagonian Sublime provides a vivid, accessible, and cutting-edge investigation of the green economy and New Left politics in Argentina. Based on extensive field research in Glaciers National Park and the mountain village of El Chalten, Marcos Mendoza deftly examines the diverse social worlds of alpine mountaineers, adventure trekkers, tourism entrepreneurs, seasonal laborers, park rangers, land managers, scientists, and others involved in the green economy. Mendoza explores the fraught intersection of the green economy with the New Left politics of the Nestor Kirchner and Cristina Fernandez de Kirchner governments. Mendoza documents the strategies of capitalist development, national representation, and political rule embedded in the 'green productivist' agenda pursued by Kirchner and Fernandez. Mendoza shows how Andean Patagonian communities have responded to the challenges of community-based conservation, the fashioning of wilderness zones, and the drive to create place-based monopolies that allow ecotourism destinations to compete in the global consumer economy."--